2021
DOI: 10.3390/ijerph182010866
|View full text |Cite
|
Sign up to set email alerts
|

Is Self-Efficacy Related to the Quality of Life in Elite Athletes after Spinal Cord Injury?

Abstract: Background: A spinal cord injury (SCI) is a traumatic event that affects every aspect of life: physical, mental, economic, and social. The main aim of this study was to investigate self-efficacy, quality of life, and their correlations among outstanding athletes who have suffered spinal cord injuries, and to determine whether these individuals have specific psychological characteristics that contribute to a better quality of life. Methods: The study involved nine athletes with at least national-level achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Self‐efficacy is an important factor influencing QoL, which is defined as faith and confidence in one's ability to perform a specific action to achieve a goal 7,8 . It has been found to be correlated with QoL in many chronic diseases, including cancer, 9 stroke, 10 spinal cord injury, 11 diabetes 12 and so on. Notably, self‐efficacy is not a fixed trait and can be modified through psychosocial interventions.…”
Section: Background For the Studymentioning
confidence: 99%
“…Self‐efficacy is an important factor influencing QoL, which is defined as faith and confidence in one's ability to perform a specific action to achieve a goal 7,8 . It has been found to be correlated with QoL in many chronic diseases, including cancer, 9 stroke, 10 spinal cord injury, 11 diabetes 12 and so on. Notably, self‐efficacy is not a fixed trait and can be modified through psychosocial interventions.…”
Section: Background For the Studymentioning
confidence: 99%
“…Disability acceptance can help mediate a sense of self-efficacy and positive life satisfaction in individuals with SCI and AdS may help mediate this transition [46]. Recent literature suggests that AdS provide persons with disabilities a sense of belonging and purpose [10,43], self-efficacy or confidence [8,9,44,[47][48][49], freedom and autonomy [9,50], continuity and structure [45,50], and hope and motivation [9,10,45]. Furthermore, besides recreational purposes alone, some individuals report that sports help regulate their mood and reduce stress [8,9,50].…”
Section: Intrapersonalmentioning
confidence: 99%
“…Previous qualitative studies have found that self-e cacy is an important facilitator of selfmanagement in persons with SCI [13,14]. The development of self-e cacy support interventions will not only improve the self-management of persons with SCI, but also compensate for the lack of long-term health care services [15].…”
Section: Introductionmentioning
confidence: 98%